Design of a Robust and Low-Cost Monocone Antenna Element for Use in Vehicle Roof-Mounted Antenna Arrays - Gardill, Markus; Fischer, Georg; Weigel, Robert; Kölpin, Alexander (IEEE Radio and Wireless Week, 2013)
We present the design of a wideband monocone antenna element having more than one octave impedance as well as pattern bandwidth. It is optimized for use in vehicle roof-mounted antenna arrays for spatial processing in an ultra-wideband local positioning secondary radar system, operating in the frequency range from 5 GHz to 8 GHz. We focus on a low-cost design, offering mechanical robustness, being ruggedized towards environmental influence, and achieving small physical dimensions using a protective dielectric-encapsulated design. In addition, we suggest a solderless and robust interconnection between coaxial connector and antenna element. The antenna element allows for arbitrary planar array geometries with grid spacing at the order of the lowest frequency of operation and a simple integration in any vehicle with a metallic roof.
elib2cris::1512001600,gardill2013a